Identification of Cyclamate in School Snacks and Health Complaints - Anisa Balqis Hadiana (Universitas Airlangga, 2018)
One of the requirements of safe school snacks that safe to consume is protected from synthetic food additives such as cyclamate. Abuse of cyclamate as sweetener for food or beverages by traders frequently encountered. The purpose of this research was to identify cyclamate in school snacks and health complaints in PG Az-Zahra. This study was an observational descriptive with cross sectional design. The sample consisted of two parts, the food sample and the respondents. The sample consisted of two school snacks and 40 selected respondents using simple random sampling technique. Respondents were interviewed about sex, age, type of snacks consumed, and the frequency of snacks consumption. The sample of school snacks were tested with organoleptic and laboratory to determine cyclamate. The results showed among two snacks, there was a snack contained cyclamate with 218.75 ppm. The respondents who always consumed school snacks were the most experienced health complaints. The most health complaint that experienced by respondents was cough. The advices are regular monitoring of traders hygienic and snacks sanitation by the school and the formation of healthy cafeteria at school. Hoping that people will be more aware to choose safe school snacks for children and brougth healthy meal for children at school. The goverment needs to restrict cyclamate distribution for only selected manufactures so that it can not be abused.